SELECTION THE BEST QUIZ APPLICATIONS AS LEARNING PERFORMANCE EVALUATION MEDIA USING THE ANALYTICAL HIERARCHICAL PROCESS METHOD - Rido Dwi Kurniawan Kurniawan; Refgiufi Patria Avrianto; Richardus Eko Indrajit; Erick Dazki (Informatika, Universitas Jenderal Soedirman, 2022)
The existence of the COVID-19 pandemic requires the whole world to limit activities outside the home, including in the world of education that uses a learning system from home. To facilitate learning activities, relevant media are needed, currently there are many recommendations for quiz applications with various interesting features. With the selection of the right learning application, it is hoped that online learning activities can run more pleasantly and be easily accepted by teachers and students. In this study, analysis and comparison was carried out with the most widely used quiz applications such as Kahoot, Quizizz, Mentimeter, Quizlet, and Educandy based on the features available in the selected quiz application. The five apps were rated based on the criteria: Security, Easy to Use, Features, Stable Connectivity, Results and feedback for Identification on the best quiz apps. Then the assessment will be analyzed and processed using the Analytical Hierarchy Process (AHP) method with the help of the AHP Calculator application. The results of this study, Kahoot ranks first with a score of 27.7%, followed by Quizizz with a score of 24.3% and then Educandy with 19%, then Mentimeter with 16% and in the last place there is Quizlet with a value of 13%. In addition, it is also known that the AHP method is very suitable for use in the decision-making process with multi-criteria and multi-alternatives, as well as decisions in choosing the quiz application method, because this method shows the results of a weighting comparison between criteria and alternatives.